Analysis of the Implementation of Communication Strategies by The Bekasi City General Election Commission (KPU) and Their Effectiveness in Increasing Voter Participation in the 2024 Election - Fauzi, Afif; Supriyatno, Budi; Hakim, Aziz (Dinasti Publisher, 2025)
This study examines the communication strategies of the Bekasi City General Election Commission (KPU) and their effectiveness in increasing voter participation in the 2024 Election. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The findings show that KPU Bekasi implemented an integrated communication strategy combining information dissemination, voter education, and institutional image strengthening. Key programs—such as Sambangi Sekolah, CYCOLATIVE, first-time voter education, and the Ayo Mencoblos campaign across 24 districts—successfully engaged young voters and diverse community groups. Digital platforms, including Instagram, YouTube, and the SIKADEKA system, further enhanced transparency and public accessibility to electoral information. The strategy contributed to an increased voter turnout of 81.3% in 2024, accompanied by stronger public trust in the election management body. Supporting factors included internal coordination, technological adaptation, and collaboration with local actors, while challenges involved limited resources, uneven political literacy, and the spread of digital misinformation. Overall, the communication strategy proved effective and adaptive, offering practical insights for strengthening democratic participation at the local level.